Investigation on the Pathological Mechanism of Frequent Exacerbators With Chronic Obstructive Pulmonary Disease Based on the Characteristics of Respiratory Flora - Ke, Li; Chen, Luo; Yaling, Yuan; Can, Gao; Jun, Lin; Chuan, Zhang (Frontiers in Medicine, 2022)
COPD is a common obstructive respiratory disease characterized by persistent respiratory symptoms and limited airflow due to airway obstruction. The present study aimed to investigate the distribution characteristics of respiratory tract flora in both frequent and infrequent exacerbators of COPD. 16S sequencing technique was adopted to differentiate the inherent differences of respiratory tract flora between frequent exacerbators and infrequent exacerbators. Additionally, cell counting kit 8 (CCK8), Lactate dehydrogenase (LDH) test, flow cytometry, enzyme-linked immunosorbent assay (ELISA) and western blot were carried out in human bronchial epithelial cells cultured in vitro and the regulatory effects of differential flora were verified. The results revealed that Observed species index, Chao1 index and ACE index of COPD frequent exacerbators were markedly higher than those of COPD infrequent exacerbators. The top five strains of COPD frequent exacerbators included g_Streptococcus (15.565%), g_Prevotella (10.683%), g_Veillonella (6.980%), g_Haemophilus (5.601%) and g_Neisseria (4.631%). Veillonella parvula generated obvious cytotoxicity and substantially reduced the activity of human bronchial epithelial cells (p < 0.01). Furthermore, the results of flow cytometry indicated that the proportion of human bronchial epithelial cells in both S phase and G2 phase decreased following Veillonella parvula treatment, indicating that Veillonella parvula inhibited cell proliferation. Meanwhile, being treated using Veillonella parvula, the expressions of interleukin-1 (IL-1), IL-6, Tumor Necrosis Factor α (TNF-α) and p-NF-κB of the cells increased markedly (p < 0.01). Taken together, the current research demonstrated that the relative abundance of Veillonella in COPD frequent exacerbators was higher than that of infrequent exacerbators. Veillonella parvula activated the inflammatory pathway, ultimately destroyed the cell viability, and greatly impaired the activity of human bronchial epithelial cells, thereby inhibiting cell proliferation.